2021
DOI: 10.3390/app11104383
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Aerodynamic Separation of Preliminarily Stratified Grain Mixture in Vertical Pneumatic Separation Duct

Abstract: The productivity of most grain cleaning machines seems to be directly related to the efficiency of vertical pneumatic separation ducts. Nevertheless, improvement is accompanied by an increase in the load of the vertical duct, the design of which is limited by the width of the grain cleaning machines. This requires an increase in the thickness of the layer of grain mixture that enters the working area of the duct, which significantly worsens the conditions of separation of its components under the action of air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The distribution of other organic impurities was consistent with the results reported by Salarikia et al 4 that other organic impurities in wheat mainly concentrated in the periphery of the silo. Kharchenko et al 22 also reported the same movement track of light impurities in the experiment of impurity separation of small grain heap, and the trajectory of light impurities in the separation from grain mixture was concave parabola. On the one hand, the gathering of other organic impurities near the silo wall would affect the ow characteristics of grains during grain unloading, and the possibility of arching was increased during unloading.…”
Section: Discussionmentioning
confidence: 70%
“…The distribution of other organic impurities was consistent with the results reported by Salarikia et al 4 that other organic impurities in wheat mainly concentrated in the periphery of the silo. Kharchenko et al 22 also reported the same movement track of light impurities in the experiment of impurity separation of small grain heap, and the trajectory of light impurities in the separation from grain mixture was concave parabola. On the one hand, the gathering of other organic impurities near the silo wall would affect the ow characteristics of grains during grain unloading, and the possibility of arching was increased during unloading.…”
Section: Discussionmentioning
confidence: 70%
“…Making use of the gravitational field predetermines limited specific performance. This is one of the basic important disadvantages of such separators [5]. As a result, in order to find effective techniques for GM separation, interest in centrifugal separators has increased.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The main difference between these equations is the introduction of additional components for the mass force in (5). Indeed, the transition to relative motion leads to the addition of real mass force (gravity) by force of inertia.…”
Section: Establishing the Defining Parameters For The Process Of The Pneumatic Vibratory Centrifugal Separation Of Grain Materials Based mentioning
confidence: 99%
“…Vertical flows provide a higher separation quality with small grain material feeds into the pneumatic separation channel [2][3][4]. With an increase in the supply of material, the efficiency of their fractionation decreases.…”
Section: Introductionmentioning
confidence: 99%
“…Another way to increase the productivity and quality of cleaning and fractionation of grain material in a vertical channel is the use of multi-flow introduction of grain material into the channel [3,11,[17][18][19]. At the same time, grain streams (monolayers) are formed, which create grain microchannel when the grain material is introduced into the air flow.…”
Section: Introductionmentioning
confidence: 99%